Sexually assaulted women: Results of a retrospective analysis of 850 women in Germany. (July 2020) - Fryszer, Lina A.; Hoffmann-Walbeck, Hannah; Etzold, Saskia; Möckel, Martin; Sehouli, Jalid; David, Matthias
Abstract: Objective: According to prevalence studies, at least 5–6 % of women in Europe experience rape in their lives. The initial treatment after a sexual assault can influence the individual healing process positively. In Germany, there are hardly any studies that investigate larger collection of cases of sexual assault treated in hospitals. However, knowledge about characteristics of cases of sexual assault is a prerequisite for the optimal processing of primary care. Study design: For this study, the retrospective collection of data on cases of suspected sexual assault of patients presented for treatment at the Charité was carried out. Standardized findings sheets as part of a rape kit used in all cases were evaluated. Overall, 850 cases from the period between 01.01.2011 and 30.06.2016 were analyzed. The statistical evaluation was descriptive. Results: The median age of patient was 26 years (range 16–92). Penetration (vaginal/anal/oral) occurred in 75 % of cases. The suspect was unknown to 48, 4 % of those affected, 26 % came from a circle of friends or acquaintances. 15, 5 % were partners or expartners. 2/3 of the sexual assaults took place in private rooms, especially in the apartments of the victims. More than 2/3 of the women had drunk alcohol in temporal proximity to the crime. Extragenital injuries were present in 61, 4 % of those affected and anogenital injuries in 25, 4 %. Extragenital injuries were predominantly classified as mild (92, 9 % in general physical examination and 62, 4 % in eyes-nose-throat-examination). 42, 1 % of the assaults took place on the weekend. 74, 8 % of the patients presented themselves within 24 h of the suspected offence. Conclusion: To our knowledge, this is the largest analysis of cases of sexually assaulted women treated at a hospital in Germany. The results point to important components of primary care, e.g. standardized injury recording and alcohol measurement, as these can serve as evidence in subsequent court proceedings. The structures of the first care of victims after sexual assault should consider that the majority of those affected present themselves at the weekend.